The ideal technique for processing SpyBite tissue specimens: a prospective, single-blinded, pilot-study of histology and cytology techniques - Baars, Judith E.; Keegan, Mathew; Bonnichsen, Mark H.; Aepli, Patrick; Theyventhiran, Ruben; Farrell, Elizabeth; Kench, James G.; Saxena, Payal; Kaffes, Arthur J. (Endoscopy International Open, 2019)
Background and study aims Diagnostic sensitivity for indeterminate biliary lesions remains suboptimal. Cytology techniques may mitigate the impediment of small cholangioscopic specimens. Our primary aim was to compare cell block cytology (CB) with standard histology for foregut SpyBite (SB) specimens. Our secondary aim was to assess CB in biliary SB biopsies.Patients and methods This was a two-phase prospective pilot study. In phase one, a prospective pilot study, foregut SB specimens from three sites (4 per site per patient per processing technique) were allocated to CB or histology, and assessed by a single, blinded pathologist. The gold standard comprised two standard forceps (CFB) histological specimens per site per patient. Specimen ease of processing, size and number, adequacy for diagnosis and artefact were evaluated. In phase two, CB was used for consecutive patients with indeterminate biliary lesions, and compared with phase one CB results.Results In phase one, 240 SB foregut biopsies were performed in 10 patients, 227 specimens recorded by pathologist. Specimen origin was identified in 100 % and 97 % of histology and CB batches respectively. Specimens were significantly larger in the histology group (2.02 mm vs 1.49 mm, P < 0.05). There was a trend to less crush artifact with CB, and no difference in processing difficulty. In phase two, 11 patients (63.0 ±12.7 years, 91 % female) underwent SpyGlass (SG) assessment of suspected indeterminate stricture (n = 8) or mass (n = 3), and six underwent SB. All CB specimens were adequate for diagnosis. Specimen parameters were not significantly different from luminal CB outcomes.Conclusions In this pilot study, cell block cytology showed similar results as histological analysis of SpyBite specimens in the analysis of biliary stricture.